Implementasi Aplikasi Penyaluran Pupuk Bersubsidi Pada Wilayah Kecamatan Unter Iwes Menggunakan Metode Rapid Application Development - Akhir Putra, Juniardi; Annursida, Arif; Mulyanto, Yudi; -, Yuliadi (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
Management of distribution and sales of subsidized fertilizer is critical to support farmers' productivity and income—however, the system used by UD. Wahyu, as a subsidized fertilizer distribution kiosk, is still manual, causing several problems. This research aims to design a web-based information system for distributing and selling subsidized fertilizer using the Rapid Application Development (RAD) method. The research method used is a web-based software development method using the RAD model. System specifications include admin, user and owner features. The data collection method uses a qualitative method with stages including observation, interviews and literature study. The system was developed using the Laravel framework and MySQL database. The research results are a web-based application to manage the distribution and sale of subsidized fertilizer. Applications can make it easier to record stock and sales, monitor distribution, and increase the transparency of the sales process. With this application, it is hoped to improve the efficiency and effectiveness of subsidized fertilizer management by UD. Revelation and provide benefits for farmers.